Efecto combinado de inductores de resistencia, tierra de diatomeas y fungicidas sobre la roya (Puccinia spp.) y rendimiento del maíz - Sabando Delgado, Miguel Alberto (2025)
The present research was conducted at the El Junquillo site, belonging to Santa Teresa parish, Chone canton, Manabí province, where the combined effect of resistance inducers, diatomaceous earth, and fungicides on diseases and yield of maize (Zea mays L.), hybrid Advanta 9735, was evaluated. A completely randomized block design with eight treatments and three replications was employed. The treatments consisted of the individual and combined application of the aforementioned products. Phytosanitary variables such as incidence and severity of foliar diseases, as well as agronomic yield variables, were evaluated. The results indicated that the treatment combining diatomaceous earth + resistance inducer + fungicide showed the lowest incidence and severity of diseases, as well as the highest grain yield. This study demonstrates that the combination of inputs can be an effective strategy to improve maize crop health and productivity, contributing to more sustainable agriculture.